Comparison of Comprehension of English Language Question Song Based on Audio Listening and Text Reading Activities - Reza Maylano F; Wiyaka Wiyaka; Ngasbun Egar (Syntax Idea)
This research is research based on the world of education which is related to the examination process which is usually related to level advancement carried out at the high school level. This research refers to research on listening tests compared to reading tests on English language arts works. Participants were given two types of input, where previously participants were divided into two groups. Listening test group and reading test group. The listening test group was given the task of listening to audio in the form of a song being played. The reading group was given treatment in the form of being asked to read a text containing the lyrics of the song played to the listening group. This research is quantitative research that uses numerical data in the form of student grades, the analysis uses regression analysis, namely analysis that correlates variables, the analysis tool uses the SPSS application and also ANOVA analysis. As a result, the difference in results from the type of test was not very significant, and it turned out that personality type had no effect on test results or final test scores.